Interactive Listening E-Modules for EFL Students: Using Canva as a Learning Tool - Julianti, Dhevy; Siminto, Siminto; Widiastuty, Hesty (Universitas Muhammadiyah Barru, 2025)
This research aims to create a learning medium for English language learners using the digital design platform Canva. The subjects of this study were 22 students from Class VIIIA at Miftahul Jannah Palangka Raya. This research employed a Research and Development (R&D) approach utilizing the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The instruments utilized for the purposes of data collection pertaining to validation and trial phases were interviews and questionnaires. The data were analyzed, both qualitatively and quantitatively. The validation results of the e-module listening indicate that the ratings from media experts were 90.7% and from material experts were 100%, which can be categorized as very feasible. A small group test was done on six Class VIIIA students using a random sampling technique, yielding a percentage result of 9.27%. Meanwhile, the large group test yielded a percentage of 93.88%, which was classified as very commendable. The results of this study help teachers in teaching and provide supporting media for students. Theoretically, this research aligns with Vygotsky's theory of social interaction, which posits that listening to audio represents a form of human interaction with media. The practical implications of this research are that it provides a basis for the development of interactive listening e-modules for use in listening learning.